POPULATION’S PERCEPTION OF THE AMOUNT AND PERIODS OF RAINFALL IN VILHENA, RONDÔNIA - de Aquino, Rafael Norberto; do Nascimento Santos, Gisely Storch; do Nascimento Cardoso, Mateus; de Castro Tolentino, João Paulo (Seven Editora, 2025)
This article aims to analyze the population’s perception of changes in the amount and periods of rainfall in the southern region of Rondônia, focusing on the city of Vilhena-RO. The theme is relevant in the face of the growing debate on the effects of climate change on regional dynamics and on the daily lives of local populations. The methodology used was descriptive, with a qualitative-quantitative approach, based on the application of structured questionnaires containing closed questions. The instruments were applied in person in different parts of the city and virtually through the Google Forms platform, being disseminated on social networks. The data revealed that 70.3% of the participants noticed a significant decrease in the amount of rainfall in recent years, while 60.4% indicated that the dry periods are longer. Also, 34.7% reported that the rains have occurred outside the periods considered traditional. These results indicate a collective perception of change in the local rainfall regime, which is consistent with scientific studies on the subject in the Amazon region. Analysis of the open responses allowed the identification of concerns related to water supply, agriculture and rising temperatures. It is concluded that the environmental perception of the population of Vilhena represents an important source of information for the formulation of public policies and educational actions aimed at mitigation and adaptation to climate change. The study reinforces the importance of considering local knowledge and the dialogue between science and society as a strategy for building sustainable and socially engaged responses to contemporary environmental transformations. DOI: https://doi.org/10.56238/sevened2025.029-016